High-Grade Glioma of the Ventrolateral Medulla in an Adult: Case Presentation and Discussion of Surgical Considerations - Angela Spurgeon; Viet Le; Sanjay Konakondla; Douglas C. Miller; Tamera Hopkins; N. Scott Litofsky (Case Reports in Neurological Medicine)
Background. High-grade gliomas of the brainstem are rare in adults and are particularly rare in the anterolateral medulla. We describe an illustrative case and discuss the diagnostic and treatment issues associated with a tumor in this location, including differential diagnosis, anatomical considerations for options for surgical management, multimodality treatment, and prognosis. Case Description. A 69-year-old woman presented with a 3-week history of progressive right lower extremity weakness. She underwent an open biopsy via a far lateral approach with partial condylectomy, which revealed a glioblastoma. Concurrent temozolomide and radiation were completed; however, she elected to stop her chemotherapy after 5.5 weeks of treatment. She succumbed to her disease 11 months after diagnosis. Conclusions. Biopsy can be performed relatively safely to provide definitive diagnosis to guide treatment, but long-term prognosis is poor.